Improving Student Learning Outcomes on the Asmaul Husana Material by Implementing the Discovery Learning Method at SD Negeri Pasi Aceh - Nuria Asra; Safra (Journal of Indonesian Primary School, 2025)
This research was conducted to improve the learning outcomes of Asmaul Husna's material in grade IV students of SD Negeri Pasi Aceh through the application of the Discovery Learning method. The research is a Class Action Research. which is carried out in two cycles with stages of planning, implementation, observation, and reflection. The subjects of the study were all grade IV students totaling 15 children; Initial data showed an average pre-cycle score of 67.2 with 6 students (40%) achieving KKM 70. The implementation of actions in the first cycle showed an increase in student activity and understanding so that the average score increased to around 71 with 9 students (60%) completed. Instructional improvements and reinforcement in cycle II resulted in significant improvements; The average class reached the range of 84 and 13 students (87%) met the KKM, indicating that the completion target was achieved. Data was collected through tests, observation of teacher and student activities, questionnaires, and documentation, and then analyzed descriptively, quantitatively and qualitatively to assess changes in achievement and learning behavior. In conclusion, the application of Discovery Learning is effective in improving Asmaul Husna's learning outcomes and student activity in the context of this class.